Simulation Comparison of Several MPPT Methods for Photovoltaic Generation - WENG Xing; ZHAO Zhengming; HE Fanbo (Kongzhi Yu Xinxi Jishu)
Various MPPT algorithms such as perturbation & observation method, incremental conductance method, etc. were analyzed by simulation at Matlab/Simulink platform based on the same converter circuit, and also were compared in misjudgment, steady-state oscillation, dynamic performance, cumulative power generation, etc. An environment condition that the solar radiation is in linear variation with time was adopted to make the simulation closer to the actual situation. In addition, a deeper theoretical comparison of perturbation & observation method and incremental conductance method were made based on mathematical explanation and geometric interpretation. Both of the simulation results and theoretical analysis show that there is no significant difference between the two methods.